Benserazide, a cystathionine beta-synthase (CBS) inhibitor, potentially enhances the anticancer effects of paclitaxel via inhibiting the S-sulfhydration of SIRT1 and the HIF1-α/VEGF pathway - Zhao, Wei; Feng, Shasha; Wang, Jian; Zhang, Zhenshuai; Chen, Lu; Jiang, Li; Li, Ming; Wang, Tianxiao (Frontiers in Pharmacology, 2024)
Cancer targeted therapy is essential to minimize damage to normal cells and improve treatment outcomes. The elevated activity of Cystathionine beta-synthase (CBS), an enzyme responsible for producing endogenous hydrogen sulfide (H2S), plays a significant role in promoting tumor growth, invasiveness, and metastatic potential. Consequently, the selective inhibition of CBS could represent a promising therapeutic strategy for cancer. Currently, there is much interest in combining paclitaxel with other drugs for cancer treatment. This study aimed to investigate the efficacy of combining benserazide, a CBS inhibitor, with paclitaxel in treating tumors. Firstly, we demonstrated CBS is indeed involved in the progression of multiple cancers. Then it was observed that the total binding free energy between the protein and the small molecule is -98.241 KJ/mol.The release of H2S in the group treated with 100μM benserazide was reduced by approximately 90% compared to the negative control, and the thermal denaturation curve of the complex protein shifted to the right, suggesting that benserazide binds to and blocks the CBS protein. Next, it was found that compared to paclitaxel monotherapy, the combination of benserazide with paclitaxel demonstrated stronger antitumor activity in KYSE450, A549, and HCT8 cells, accompanied by reduced cell viability, cell migration and invasion, as well as diminished angiogenic and lymphangiogenic capabilities. In vivo studies showed that the combined administration of benserazide and paclitaxel significantly reduced the volume and weight of axillary lymph nodes in comparison to the control group and single administration group. Further mechanistic studies revealed that the combination of benserazide and paclitaxel significantly suppressed the Ssulfhydration of SIRT1 protein, thereby inhibiting the expression of SIRT1 protein and activating SIRT1 downstream Notch1/Hes1 signaling pathway in KYSE450, A549, and HCT8 cells. Meanwhile, we observed that benserazide combined with paclitaxel induced a more significant down-regulation of HIF-1α, VEGF-A, VEGF-C, and VEGF-D proteins expression levels in KYSE450, A549, and HCT8 cells compared to paclitaxel alone. These findings indicated that benserazide enhances the anticancer effects of paclitaxel via inhibiting the S-sulfhydration of SIRT1 and down-regulating HIF-1α/VEGF signaling pathway. This study suggests that benserazide may have potential as a chemosensitizer in cancer treatment.